Thermal imaging to evaluate healing of burn wounds treated with colloidal nano silver hydrogel and decellularised bovine omentum in a rat model - Reji Varghese; S. Anoop; Syam K. Venugopal; S. Sooryadas; V.N. Vasudevan; Varuna P. Panicker; Sudheesh S. Nair; K.D. John Martin (Journal of Veterinary and Animal Sciences)
Infrared thermography is a safe, non-invasive and inexpensive imaging technique used for the assessment of depth of burn wounds. The present study was aimed at evaluation of burn wounds from the day of infliction till complete healing using thermography and compare it with the gross morphology and histopathology. Burn wounds were induced in Wistar rats under general anaesthesia followed by excision and grafting, 72 hours after the infliction of burn injury. Colloidal nano silver was used as the topical medication and decellularised bovine omentum was used as the scaffold. Thermography was performed on the day of infliction of burn injury and grafting, and on 3rd, 7th, 14th and 21st day thereafter. The thermal images were compared with the gross morphological changes and histopathological findings. The thermal images gave a different perspective of the burn wounds on the day of infliction and after 72 hours. Though the changes were comparable with gross morphology and histopathology from day 0 (after grafting) till complete healing, thermography seemed to be over-representing the inflammatory changes. The increased peri-wound temperatures indicated a healing wound. It could be concluded that infrared thermography could be effectively used for burn wound monitoring in the clinical scenario and as a complimentary tool for burn wound research.